The 18-year risk of cancer, angioedema, insomnia, depression, and erectile dysfunction in association with antihypertensive drugs: post-trial analyses from ALLHAT–Medicare linked data - Du, Xianglin L.; Martinez, Journey; Yamal, Jose-Miguel; Simpson, Lara M.; Davis, Barry R. (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To determine the 18-year risk of cancer, angioedema, insomnia, depression, and erectile dysfunction in association with antihypertensive drug uses.Methods: This is a post-trial passive follow-up study of Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) participants in 1994-1998 by linking with their Medicare claims data through 2017 among subjects who were free of outcomes at baseline on January 1, 1999. Main outcomes were the occurrence of cancer (among n=17,329), angioedema (among n=17,340), insomnia (among n=17,340), depression (among n=17,330), and erectile dysfunction (among n=7,444 males) over 18 years of follow-up.The 18-year cumulative incidence of cancer other than non-melanoma skin cancer from Medicare inpatient claims was 23.9% for chlorthalidone, 23.4% for amlodipine, and 25.3% for lisinopril. There were no statistically significant differences in the 18-year risk of cancer, depression and erectile dysfunction between the 3 drugs based on the adjusted hazard ratios.The adjusted 18-year risk of angioedema was elevated in those receiving lisinopril than those receiving amlodipine (hazard ratio: 1.63, 95% CI: 1.14-2.33) or those receiving chlorthalidone (1.33, 1.00-1.79), whereas the adjusted 18-year risk of insomnia was statistically significantly decreased in those receiving lisinopril than those receiving amlodipine (0.90, 0.81-1.00).The 18-year risk of angioedema was significantly higher in patients receiving lisinopril than those receiving amlodipine or chlorthalidone; the risk of insomnia was significantly lower in patients receiving lisinopril than those receiving amlodipine; and the risk of cancer, depression, and erectile dysfunction (in men) was not statistically significantly different among the 3 drug groups.